Onset of complications following cervical manipulation due to malpractice in osteopathic treatment: A case report. (October 2014) - Cicconi, Michela; Mangiulli, Tatiana; Bolino, Giorgio
The aim of this study is to correlate cervical disc herniation with manipulation performed by a non-physician osteopath on a patient complaining of neck pain. The authors report a case in which a woman – treated with osteopathic spinal manipulation – developed cervical-brachial neuralgia following the cervical disc herniation. The patient then underwent surgery and was followed by physiotherapists. A clinical condition characterized by limitation of neck mobility, with pain and sensory deficit in the right arm and II–III fingers, still persists. The patient consulted the authors to establish whether cervical disc herniation could be attributed to manipulation. Adverse events or side effects of spinal manipulative therapy are relatively common and usually benign. Most of these side effects are mild or moderate, but sometimes they can be severe. Cervical manipulation can provoke complications less often than thoracic or lumbar manipulation. Furthermore, many diseases can be absolutely and relatively contraindicated to osteopathic treatment. Therefore, the knowledge of a patient's clinical conditions is essential before starting a manipulative treatment; otherwise the osteopath could be accused of malpractice. It is the authors' opinion that a cause–effect relationship exists between the manipulative treatment and the development of disc herniation.